Physical Activity among Adolescents in Urban and Rural Area in South Sulawesi, Indonesia: Exploring the Influence of Environmental Factors - Rezky Aulia Yusuf; Farihah Muhsanah; Alya Dafa Amirah; Syiar Cakke (CV. Global Health Publication, 2026)
Background: Neighbourhood environments play an important role in shaping adolescents’ physical activity (PA), yet environmental influences differ between urban and rural settings. Understanding these contextual differences is essential for developing effective strategies to promote PA among adolescents. Aim: This study aimed to explore environmental determinants influencing adolescents’ participation in physical activity in urban and rural areas. Method: A qualitative study was conducted using a snowball sampling technique. Twenty adolescents aged 13–15 years participated in offline and online semi-structured interviews comprising 17 questions. The photovoice method was used to support data collection. All interviews were analysed thematically using NVivo 12 software. Results: Rural adolescents reported access to natural environments such as hills and small forests; however, limited awareness, poor management, inadequate infrastructure, long distances, road safety issues, and a lack of recreational facilities restricted their use for PA. Urban adolescents had access to safe, clean, and diverse sports facilities but often engaged in sedentary behaviours, particularly excessive use of smartphones and tablets during leisure time. Conclusion:Targeted health promotion and PA education programmes are needed, particularly in urban areas, to reduce sedentary behaviour. In rural settings, improving basic infrastructure and optimising natural resources may provide cost-effective and sustainable approaches to promote adolescent physical activity.